Behavior of some Hungarian wheat varieties to seed soaking in gibberellic acid under salt stress - Abido, W. A. E.; Zsombik, László (Acta Agraria Debreceniensis, 2017)
Various abiotic stresses including high salinity strongly affect seed germination. Three Hungarian wheat landraces Gamási, Fóti and Kartali have been tested for seed germination, seedling growth and chemicals parameters when seeds were soaked in gibberellic acid (GA3) at the concentrations of 0, 75 and 150 ppm and at four levels of salinity stress 0, 5, 10 and 15 dSm-1. A laboratory experiment took place at Research Institute of Nyíregyháza. Factorial Experiment based on Randomized Complete Block Design (RCBD) in four replications has been conducted. Seed soaking in GA3 before sowing significantly affected germination characteristics, seedling properties and the results of chemical analysis. The highest germination as well as K+ content of seeds were observed at seed soaking into 150 ppm GA3. However, Na+ and proline contents in seedling were decreased. The behavior of the tested Hungarian wheat varieties was genotype-dependent. Increasing salinity stress up to 15 dSm-1 significantly affected germination characteristics, seedlings parameters and chemical analysis. Fóti variety turned out to be the best at 150 ppm GA3 compared to the other two varieties. Moreover, it had the lowest Na+ and proline contents and highest K+ content.